Formulation development of Silybum marianum seed extracts and silymarin nanoparticles, and evaluation of hepatoprotective effect - Macit, Meltem; Duman, Gülengül; Cumbul, Alev; Sümer, Engin; Macit, Çağlar (Editions de Sante, 2023)
In this study, we formulated silymarin-nanoparticles and assayed their ability to reduce acetaminophen-induced toxicity in vitro and in vivo. After silymarin molecules were encapsulated the loading efficiency and the physicochemical properties of fabricated nanoparticles were investigated by HPLC and DLS analysis. The in vivo hepatoprotective studies were conducted on rats in an optimized setting. The nanoformulation was presented a significant (p ? 0.05) hepatoprotective effect by reducing the serum marker enzymes such as AST, and ALT. The histopathological study further confirmed the hepatoprotective activity of the nanoformulations when compared with the acetaminophen-induced, two different silymarin formulations as treatment group and control group. These results indicate that the nano approaches could be used to improve the therapeutic efficacy of the nano-silymarin. The formulation of silymarin-nanoparticles showed a spherical shape with an average diameter between 138.9 nm and 1155 nm, the zeta potential of – 0.0340 mV. The average loading efficiency was found around 32 ± 0.5%.
Keywords: ALT and AST; Extraction; Liver; Milk Thistle; Silymarin